2020
DOI: 10.1515/tjj-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flow Distortion Generated Forced Response of a Radial Turbine with Vaneless Volute

Abstract: For a radial turbine with vaneless volute, the inflow of turbine rotor usually has a circumferential flow distortion due to the influence of the volute tongue. The rotating blades of the rotor are exposed to harmonic aerodynamic loads caused by the distortion, which may induce rotor resonance and lead to high cycle failures (HCF). To understand the forced response mechanism clearly, a numerical analysis was carried out based on a fluid structure interaction (FSI) method. The pressure functions were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Via numerical simulations of a twin-entry scroll with full turbine blades, Yokoyama et al (2014) studied the flow phenomena caused by engine exhaust pulsation and identified the characteristics of the flow processes that cause losses. Huang et al (2020) used an approach based on fluid–solid interaction to simulate an RT with a vaneless volute and examine the circumferential flow distortion of the turbine rotor caused by the volute tongue.…”
Section: Introductionmentioning
confidence: 99%
“…Via numerical simulations of a twin-entry scroll with full turbine blades, Yokoyama et al (2014) studied the flow phenomena caused by engine exhaust pulsation and identified the characteristics of the flow processes that cause losses. Huang et al (2020) used an approach based on fluid–solid interaction to simulate an RT with a vaneless volute and examine the circumferential flow distortion of the turbine rotor caused by the volute tongue.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the turbocharger turbine wheel design needs to be more efficient, with a thinner blade thickness to meet the performance and low-speed response requirements, which makes the turbocharger turbine high-cycle-fatigue failure mode more prominent. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the turbocharger turbine wheel design needs to be more efficient, with a thinner blade thickness to meet the performance and low-speed response requirements, which makes the turbocharger turbine high-cycle-fatigue failure mode more prominent. 4,5 At present, the unsteady excitation problem of turbine wheels for automotive turbochargers has been extensively investigated. These investigations have mainly focussed on the interaction between the guide vane of the variable geometry turbocharger or variable nozzle turbine turbocharger and the turbine wheel, namely, the rotor-stator interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For a vaneless turbine, the flow distortion in the circumferential direction at volute exit is the most important source of aerodynamic excitation. Huang et al 10 discovered that a region of high pressure and low momentum appears downstream of the volute tongue, which is caused by the mixing of tongue wake and mainstream flow. When a blade sweeps by the tongue, pressure on the blade fluctuates drastically due to flow distortion, leading to blade excitation.…”
Section: Introductionmentioning
confidence: 99%